Long-term effectiveness of the Mindful Self-Compassion programme compared to a Mindfulness-Based Stress Reduction intervention: a quasi-randomised controlled trial involving regular mindfulness practice for 1 year - Crego, Antonio; Yela, José Ramón; Gómez-Martínez, María Ángeles; Sánchez-Zaballos, Elena; Vicente-Arruebarrena, Aitor (Frontiers in Psychology, 2025)
IntroductionThis study compares the Mindful Self-Compassion (MSC) programme with the Mindfulness-Based Stress Reduction (MBSR), a well-established intervention, and a control group, and includes 1 year of continuous practice.MethodsA longitudinal quasi-RCT was conducted with measurements at baseline, post-training, 6 months and 1 year. A total of 170 individuals (75.9% female) were randomly assigned to the MSC (n = 48) and MBSR (n = 65) groups, with a non-fully randomised wait-list CG (n = 57).ResultsUsing intention-to-treat (ITT) and per-protocol (PP) analysis strategies, results consistently indicated that standard 8-week MSC and MBSR trainings produced benefits on anxiety, depression, perceived stress, and positive and negative affect, as well as on variables related to psychological flexibility, compared with CG. These gains were maintained over a year of continuous practice in both training groups. Overall, the two programmes, MSC and MBSR, showed a similar trajectory over the measurement periods.DiscussionThe 8-week MSC programme and the regular practice of mindfulness and self-compassion appear to be an effective intervention for promoting mental health in the general population, with benefits similar to those derived from the practice of exercises from well-known mindfulness programmes such as MBSR.